The Influence of Entrepreneurial Spirit of Business Actors on MSME Performance During the Covid-19 Pandemic in Palopo City with Digital Marketing as an Intervening Variable - Burhan Rifuddin; Fadila Muchta (Technium Social Sciences Journal, 2024)
The study examined the influence of the entrepreneurial spirit of business actors on performance. Micro, Small and Medium Enterprisesduring the covid-19 pandemic in Palopo City with digital marketing as an intervening variable. The type of research is quantitative research with a structural equation model approach. The results of the study showed that no direction of the relationship between the entrepreneurial spirit of MSME entrepreneurs (Ƹ) and the financial performance of MSME entrepreneurs (ῃ2) in Palopo City during the covid-19 pandemic, there was a real relationship or significant influence of the entrepreneurial spirit of MSME entrepreneurs (Ƹ) on digital marketing (ῃ1) during the covid-19 pandemic. there is a relationship and real or significant influence of digital marketing (ῃ1) on the performance of MSMEs (ῃ2), there is an indication, when the spirit or entrepreneurial spirit expressed in hard work activities, innovation expressed by the application of creative ideas, and creativity in the form of statements of the ability to apply something new in entrepreneurship, as well as the basis of belief in success during the Covid-19 pandemic which if quantified by 1 then marketing efforts with dropshipper or reseller activities, namely a statement of the entrepreneur’s initial understanding to understand various factors in digital marketing through copywriting, namely a statement that states arousing curiosity and interest for prospective consumers and existing consumers and thematic pacebook pages and Instagram, namely statements about efforts to attract potential buyers and buyers quickly, then the performance of MSMEs in Palopo City has increased by 0.850 or 85%. Digital marketing is able to mediate the entrepreneurial spirit of MSME business actors towards the performance of MSMEs in Palopo City during the Covid-19 pandemic.